Evaluasi Program Sarjana Membangun Desa (SMD) dan Strategi Pengembangannya (Studi Kasus Provinsi Sumatera Barat, Jawa Barat dan Nusa Tenggara Barat) - YELLY REFITA; HERMANTO SIREGAR; ARIF IMAM SUROSO (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
Sarjana Membangun Desa (SMD), or Bachelors Builds Villages, is a program that places undergraduate degree holders to empower livestock farmers which implemented by the Ministry of Agriculture Republic of Indonesia. This program has been started since 2007 with the number of beneficiaries has reached 2,694 groups scattered across Indonesia. This study aimed to conduct a thorough evaluation of the implementation of SMD, covering from the identification of potential region, evaluation of the effectiveness of the program and the formulation of the development strategies. The results showed that SMD has not been implemented based on the region potentials. The evaluation on the effectiveness of SMD on economic, technical and institutional indicators showed that the program has not been effective in achieving its goal. The CIPP (Context, Input, Process, and Product) evaluation showed that the causes of the ineffectiveness of the program are: (1) the program has no strategic plan; (2) lack of supports and participation from local government and communities; and (3) ineffectiveness at the selection and recruitment stage, reporting, monitoring and evaluation. Based on the result of Analytic Hierarchy Process (AHP) analysis, the strategy that needs to be put as priority to improve the effectiveness of the SMD is human resources strengthening which can be implemented through training and counseling.